Leadership and Karma: doing good or doing well? - Swaran P. Singh (BJPsych Bulletin)
Modern management has much to learn from ancient wisdoms. Management structures based on corporate trends were transferred from business to services such as healthcare to promote cost-efficiency and productivity. In this article, I argue that the short-term approach of corporate leaders being brought into healthcare for ‘transformation’ has led to a trail of service dismemberment with no discernible clinical gain for those we seek to serve. Bhagwad Gita, the ancient Hindu scripture on right conduct, is an exemplar of how the primary aim of leaders should be to provide better service rather than serve personal interests or those of the ‘business’ of healthcare.